Microemulsions and Nanoemulsions for Topical Delivery of Tripeptide-3: From Design of Experiment to Anti-Sebum Efficacy on Facial Skin - Nontachai Magrode; Worrapan Poomanee; Kanokwan Kiattisin; Chadarat Ampasavate (MDPI AG, 2024)
The targeted delivery of a hydrophilic Tripeptide-3 to the skin using microemulsions or nanoemulsions for facial oil reduction was the focus of this study. The impact factors affecting oil/water transparent dispersion formation, such as the surfactant system, HLB value, and co-solvent, were identified through the water titration method and pseudoternary phase diagram plots. The interfacial tension between caprylic/capric triglyceride (CCT oil) and water was significantly reduced by the surfactant/co-surfactant combination (Smix) of Cremophore® RH40 and a double-tails co-surfactant, polyglycerol-3-diisostearate, at an HLB of 13 together with a water-to-co-solvent (PG) ratio of 1:1. A two-level full factorial design of experiment (FFD-DoE) emphasized the independent variables of the HLB value, co-solvent, and CCT oil contents affecting the optimal compositions for micro- or nanoemulsion formation. The low-energy spontaneous emulsification of the optimized combination at a low Smix content (10%) yielded the translucent oil-in-water Tripeptide-3 nanoemulsions with an internal droplet size of 25.7 ± 1.20 nm, a narrow polydispersity index of 0.237 ± 0.129, and 70.6 ± 0.58% transmittance. The in vitro skin permeation study revealed a significantly higher skin penetration and retention of the Tripeptide-3 nanoemulsions compared to the high surfactant microemulsions and coarse emulsions. Skin irritation and oil control efficacy were evaluated in healthy volunteers before and after product application for 28 days. The obtained nanoemulsions not only decreased sebum production but also enhanced skin moisture levels. In conclusion, the meticulously designed nanoemulsions, incorporating suitable excipients, show a promising delivery system for hydrophilic peptides to control sebum overproduction in oily facial skin.